Area-based Urban Creativity Systems in Italy: What They Are and How to Recognize Them - Luca Borriello; Silvia Scardapane (European Journal of Creative Practices in Cities and Landscapes)
In the last decade, urban creativity has manifested itself in many proximity spaces, in particular, among its visual expressions, with the ‘new muralism’ (unlike ‘graffiti writing’ and ‘street art’). This has corresponded with an often-desired resignification of public spaces that has affected the geographically, politically and linguistically more marginal territories. In such uncertain areas, networks of meaning have developed, i.e., homogeneous spaces which, simultaneously or diachronically, have begun to concentrate a plurality of works in relation to the territory to which they belong and the community. This phenomenon has been investigated in the following work, which proposes the definition of urban creativity systems. The work also deepens, among the many case studies, the urban creativity program for the social called “Parco dei Murales” conceived and promoted by INWARD - National Observatory on Urban Creativity, launched in collaboration with the resident community in a social housing complex in the Ponticelli district in Naples.